Marginally Better: My Husband’s Lover And Gay Portrayal - Chadwick Co Sy Su, Chadwick Co Sy Su; R Castro, Joeven; Martin Anthony , Paul C Cenizal (2015)
My Husband’s Lover is a Philippine telenovela that has garnered critical and commercial success (and along the way catapulting its two stars to A-list status), mainly due to a premise that heavily mirrors Ang Lee’s Brokeback Mountain (2005) but that which is unique to generally conservative Philippine society. Two high school best friends Eric Del Mundo (Dennis Trillo) and Vincent Soriano (Tom Rodriguez) also happen to be high school sweethearts, with the former leaving the latter.. Likewise, the latter’s family is the typical conservative Filipino family, so he decided to conceal his homosexuality for fear of being disowned. The two reunite years later, with Eric returning from the United States and learning that his former lover is engaged and is expecting a child with Lally Agatep (Carla Abellana). The series details the continuation of Vincent’s and Eric’s (still hidden) romance, and the former’s internal conflict, that between his true feelings and his morals. The dynamics of a love triangle peculiar to the average Filipino audience separate it from the typical Filipino romantic plotline, the portrayal of homosexuality being another Philippine TV trope that has been amply twisted so that it is “fresh.” Instead of the usual flamboyant gay best friend, the homosexuals are not only far from flamboyant, but are also the main characters of the series. Instead of being staples of beauty salons speaking in seeming code that is actually gay lingo, the homosexuals are affluent and well-spoken. The authors will buttress their textual analysis of all ten seasons of My Husband’s Lover with literature on the bakla and the global gay. With queer theory as the framework of the study, with emphasis on the theory’s element of performativity, the authors will also use several significant instances throughout the ten seasons of the series as premises to one of queer theory’s assumptions, that gender is fluid.